Correlação entre habilidades cognitivo-linguísticas em escolares com dificuldades de aprendizagem - Silva, Cláudia Da; Capellini, Simone Aparecida [UNESP] (Associacao Brasileira de Psicopedagogia, 2012)
OBJECTIVE: The aim this study was to verify the existence of association between skills of same cognitive domain, of the test cognitive-linguistic performance - collective and individual version, in students with learning difficulties. METHODS: The participants of this study were 57 students from 4th grades of the elementary school, with old between 10 years and 5 months to 14 years and 7 months, of both genders. As procedure was utilized the Test Cognitive-Linguistic Performance - collective and individual version. The collective version is composed for skills of writing, arithmetic, auditory processing and visual processing, and the individual version is composed for skills of reading, phonological awareness, auditory processing, visual processing and processing speed. RESULTS: The results this study demonstrated positive correlation coefficient among the variables of the subtests, suggesting that the higher the values of a variable, the greater the values of another variable. CONCLUSION: We can conclude that the correlation of each test of the skills of the Test Cognitive-Linguistic Performance showed parallel behavior, indicating that, to the tests correlated the performance in a variable affects the performance of another, thus causing a deficit in the performance of students in classroom.

OBJETIVO: Verificar a existência de associação entre habilidades de mesmo domínio cognitivo, do teste de desempenho cognitivo-linguístico - versão coletiva e individual - , em escolares com dificuldades de aprendizagem. MÉTODO: Participaram deste estudo 57 escolares da 4ª série do ensino fundamental, com idade entre 10 anos e 5 meses a 14 anos e 7 meses, de ambos os gêneros. Como procedimento foi utilizado o Teste de Desempenho Cognitivo-Linguístico, versão coletiva e individual. A versão coletiva é composta por habilidades de escrita, aritmética, processamento auditivo e processamento visual, e a versão individual é composta por habilidades de leitura, consciência fonológica, processamento auditivo, processamento visual e velocidade de processamento. RESULTADOS: Os resultados deste estudo revelaram coeficiente de correlação positivo entre as variáveis dos subtestes, sugerindo que, quanto maiores os valores de uma variável, tanto maiores os valores da outra. CONCLUSÃO: A correlação de cada prova das habilidades do Teste de Desempenho Cognitivo-Linguístico apresentou comportamentos paralelos, indicando que, para as provas correlacionadas, o desempenho em uma variável interfere no desempenho da outra, ocasionando, assim, um déficit quanto ao desempenho desses escolares em sala de aula.
Correlation between cognitive-linguistic skills in students with learning difficulties
Keywords: Aprendizagem; Transtornos de aprendizagem; Leitura; Escrita; Learning; Learning disorders; Reading; Writing